Int. J. Adv. Res. Biol. Sci 2017
DOI: 10.22192/ijarbs.2017.04.04.004
|View full text |Cite
|
Sign up to set email alerts
|

A Comparative Study on Proximate and Antioxidant Activity of Brassica oleracea (Kale) and Spinacea oleracea (Spinach) Leaves

Abstract: Green leafy vegetables have excellent content of vitamins as well as minerals and also contain an enormous variety of bioactive components which provide health benefits beyond basic nutrition. The purpose of the study is to evaluate the proximate composition by standard AOAC method, antioxidant properties and DPPH free radicals scavenging activity of aqueous extract of Brassica oleracea and Spinacea oleracea. The study revealed that crude fiber, protein, iron and calciumcontent in Brassica oleracea was signifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…In general, dark green leafy vegetables, such as broccoli, watercress, and spinach, as well as yellow or red fruits and vegetables, are very rich in flavonoids [47,48]. When comparing the obtained results with those reported in the literature, it was observed that Brassica plants, such as broccoli and watercress, presented much lower flavonoid contents than those obtained by Agarwal et al [49] (broccoli, 13.98 mg QE/g vegetable) and Aires et al [50] (watercress, 5.6 mg CatE/g dried weight). This difference may be associated with some factors, such as geographic variation, harvest time, and environmental and agronomic conditions [51,52].…”
Section: Determination Of the Phytochemical Compositionmentioning
confidence: 57%
“…In general, dark green leafy vegetables, such as broccoli, watercress, and spinach, as well as yellow or red fruits and vegetables, are very rich in flavonoids [47,48]. When comparing the obtained results with those reported in the literature, it was observed that Brassica plants, such as broccoli and watercress, presented much lower flavonoid contents than those obtained by Agarwal et al [49] (broccoli, 13.98 mg QE/g vegetable) and Aires et al [50] (watercress, 5.6 mg CatE/g dried weight). This difference may be associated with some factors, such as geographic variation, harvest time, and environmental and agronomic conditions [51,52].…”
Section: Determination Of the Phytochemical Compositionmentioning
confidence: 57%
“…Leaves contain phenolics, polyphenols, glucosinolate, sugars, flavonoid, and flavonoids glycoside and show antioxidant activity in terms of FRAP, DPPH radical scavenging activity [38,52] B. oleracea Acephala L.…”
Section: Gemmiferamentioning
confidence: 99%
“…Generally, it was observed that the kefir‐based smoothies with vegetables had higher ash, protein, carbohydrate, glucose, and dietary fiber content. The differences in the composition of samples may be attributed to maturity, agro‐climatic conditions, agricultural practices, and frozen process of the vegetable species (Agarwal et al., 2017 ; Biondi et al., 2021 ; Satheesh & Fanta, 2020 ). Regarding vegetable‐based smoothies, the green vegetable smoothie including 6% spinach, 12% broccoli, and 77.2% cucumber was the subject of research by Castillejo et al.…”
Section: Resultsmentioning
confidence: 99%
“…There has recently been an increasing demand for both vegetables since kale contains high amounts of prebiotic compounds and spinach contains all the essential amino acids to be taken daily as recommended by the FAO nutritional standards. Both kale and spinach manifest positive health benefits including anticarcinogen, antidiabetic, antihypertensive, anti‐inflammatory, atheroprotective, gastroprotective, neuroprotective, reduction in cholesterol absorption, and prevention of bone mineral density (Agarwal et al., 2017 ; Maqbool et al., 2021 ; Natesh et al., 2017 ; Ortega‐Hernández et al., 2021 ; Papierska et al., 2022 ; Šamec et al., 2019 ; Satheesh & Fanta, 2020 ; Thakur et al., 2022 ).…”
Section: Introductionmentioning
confidence: 99%